Penerapan Strategi Curiosity Gap dalam Produksi Konten Bisnis Digital pada Akun @ravmedia.co di Instagram dan TikTok - Egialipamana Ramdini Sitepu; Aceng Hidayat (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study examines the application of the curiosity gap strategy in digital content production on the @ravmedia.co account on Instagram and TikTok platforms. This research is important to conduct considering that increasingly fierce digital content competition requires creators to understand the psychological mechanisms of audiences in attracting and maintaining attention. The purpose of the study is to analyze how the curiosity gap strategy is implemented through content elements and to identify engagement patterns associated with this strategy. The study uses Loewenstein's information gap theory as a theoretical basis, with a descriptive qualitative approach through a case study method on @ravmedia.co's featured content during the period of January–May 2026. Analysis was conducted on four content elements: the title (headline), hook, script (voiceover), and caption, alongside platform insight data. The findings indicate that the curiosity gap strategy is systematically and synergistically applied through all four elements. The Bus Simulator content on Instagram recorded an engagement rate of 9.1%, exceeding the global Instagram average of 0.48%. On TikTok, the same content achieved an engagement rate of 4.05%, surpassing the global average of 3.70%. The vast majority of viewers on both platforms came from non-followers (99.8%–100%), potentially indicating strong organic distribution capacity. These findings suggest that curiosity gap constitutes a structured communication approach that is associated with higher engagement performance and organic content distribution on social media.